1995
DOI: 10.1002/adma.19950071006
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence, photoluminescence and x‐ray reflectivity studies of self‐assembled ultra‐thin films*

Abstract: High‐qality self‐assembled heterostructures for polymer LEDs have been fabricated from PPV and newly synthesized copolymers of PPV and naphthalene. It is shown that the layer‐by‐layer self‐assembly of multilayer structures has advantages with respect to control of the thickness and homogeneity of the polymer films compared to the conventional spin coating technique. The fabrication and characterization of the heterostructures are detailed and features of the electroluminescence and photoluminescence discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 17 publications
2
55
0
Order By: Relevance
“…Hong et al reported on the characterization of LEDs from poly(styrene-4-sulfonate) (SPS) and a copolymer of PPV and naphthalene [31]. LEDs were prepared by alternative deposition of the PPV-precursor polymer as the polycation and SPS as the polyanion.…”
Section: Polyelectrolyte-based Devices W W W W W W W W W W W W W W W mentioning
confidence: 99%
“…Hong et al reported on the characterization of LEDs from poly(styrene-4-sulfonate) (SPS) and a copolymer of PPV and naphthalene [31]. LEDs were prepared by alternative deposition of the PPV-precursor polymer as the polycation and SPS as the polyanion.…”
Section: Polyelectrolyte-based Devices W W W W W W W W W W W W W W W mentioning
confidence: 99%
“…Most of the envisioned applications require incorporation of organic molecules having interesting chromophores. Studies on nonlinear optical properties ferroelectricity, pyroelectric properties , photochromic effect are going on using LB films [10][11][12][13][14] In this communication we have investigated the mixing behaviour of a laser dye Octadecyl Rhodamine B (RhB) and stearic acid in the mixed Langmuir monolayer on the water surface. Surface Pressure vs. area per molecule isotherm and fluorescence imaging microscopy (FIM) studies were used to characterize the monolayer films.…”
Section: Introductionmentioning
confidence: 99%
“…This remarkably simple technique provides molecularlevel control over the thickness and complicated architecture of multilayer magnetic, conducting, 15 and luminescent films. 16 Thus it offers a potentially powerful strategy for fabricating nanomagnetic, nanoelectronic-magnetic, nanomagnetic-optical, and nanomagnetic-electroluminescent devices.…”
mentioning
confidence: 99%